2017
DOI: 10.1177/1098611117708791
|View full text |Cite
|
Sign up to set email alerts
|

After the Stop: Exploring the Racial/Ethnic Disparities in Police Use of Force During Terry Stops

Abstract: Questions surrounding stop, question, and frisk (SQF) practices have focused almost exclusively on racial and ethnic disproportionality in the rate of stops, and whether police are engaged in racial profiling. This near-sole focus on the stop decision has overshadowed important questions about the use of force during Terry stops, resulting in a major gap in our understanding of the dynamics of SQF encounters. The current study addresses this issue through an examination of the nature, prevalence, and predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 78 publications
2
42
0
Order By: Relevance
“…The processes we identify exist alongside numerous other mechanisms that contribute to disparate outcomes, including overt discrimination (Legewie ; Morrow, White, and Fradella ; Nascimento ) and implicit bias (Correll et al ; Eberhardt et al ; Plant and Peruche ). We strongly doubt that people with more cultural capital are simply more “adept” at interacting with police (as researchers have suggested in the health care contexts [see Shim ]).…”
Section: Discussionmentioning
confidence: 91%
“…The processes we identify exist alongside numerous other mechanisms that contribute to disparate outcomes, including overt discrimination (Legewie ; Morrow, White, and Fradella ; Nascimento ) and implicit bias (Correll et al ; Eberhardt et al ; Plant and Peruche ). We strongly doubt that people with more cultural capital are simply more “adept” at interacting with police (as researchers have suggested in the health care contexts [see Shim ]).…”
Section: Discussionmentioning
confidence: 91%
“…This pattern of racial bias exists for both lethal and nonlethal forces. Once they had stopped a suspect, New York City police officers were more likely to use nonweaponized force against Black and Hispanic suspects than against White suspects, even after controlling for variables like the crime rate in the precinct, suspect demeanor, and the presence of a weapon (Morrow, White, & Fradella, ). They were also more likely to use potentially lethal force (i.e., draw a gun) against Black than White suspects (Kramer & Remster, ).…”
Section: Prevalence Of Racial Disparitiesmentioning
confidence: 99%
“…Nearly a quarter (21%; n = 4) of studies included social‐level factors. The studies that focused on more than the multi‐level factors such as social and community found that officer relationship to the suspect, geographical location, disproportionate surveillance of people of color, and discriminatory policies were key motivating factors (Jones‐Webb, Calvert, & Brady, 2018; Kahn, McMahon, & Stewart, 2018; Morrow, White, & Fradella, 2017; Motley, & Joe, 2018; Vera Sanchez & Rosenbaum, 2011).…”
Section: Resultsmentioning
confidence: 99%